Effect of ball-milling time on chemical property of coconut shell powder. (June 2020) - Ismail, I; Arliyani,; Fathmiyah, S; Mursal,; Jalil, Z; Khalil, H P S A
Abstract: Coconut is one of the abundant agricultural products in Indonesia. Coconut shell is one of the wastes from coconut products that can be used as biocomposite material. The purpose of this study was to find out the effect of ball milling time on the chemical properties of coconut shell powder. X-ray diffraction (XRD) and X-ray fluorescent (XRF) have been used in this study. Coconut shell powder 200 mesh was milled using mechanical ball milling for various milling times (20, 30, and 40 hours) at 350 rpm constant speed. The results of our study using XRD showed that the coconut shell powder contains SiO2, C, Fe2 O3, CaO, K2 O, and Al2 O3 . The intensity of the diffraction pattern from our sample increased when the ball-milling time was increased. This implies that the crystallinity of the sample was influenced by the ball-milling time. By using XRF, it was found that the coconut shell powder contains 13.6% of Fe2 O3, 25.7% of CaO, 46.1% of K2 O, 2.8% of CuO, and 8.2% of P2 O5 . The percentage composition of Fe2 O3 increased from 13.6% for 0 hours milling time to 30.2% after the sample was milled for 20 hours. The percentage composition of Fe2 O3 rose to 32.2% for the milling time of 40 hours. However, the percentage compositions of CaO and K2 O decrease as the milling time is increased. The percentage composition of P2 O5 is independent of milling time. Our results show that the chemical properties of coconut shell powder are influenced by the ball-milling time or particle size of coconut shell powder.